A study on factors that would affect job turnover among management staff within Avillion Legacy Melaka Hotel / Nur Kuaizah Adenan - Adenan, Nur Kuaizah (Faculty of Business and Management, 2010)
Job turnover is a complex and sophisticated subject, organizations around the world are facing similar business challenges which are the difficulty of attracting talent and retaining quality employees. In a human resources context, turnover or labor turnover is the rate at which an employer gains and losses employees. When looking at this problem area, we found that there have been actions that companies can use to avoid this problem. The past researcher shows that there are many factors that affect the employee’s job turnover. Present research study on three factors that could be the reasons for employees leaving the company which is career opportunities, compensation and benefits system and also job satisfaction. This study has been conducted within Avillion Legacy Melaka hotel and it involved 32 respondents in different department. Results of the present study showed that the most influential factors that affects job turnover within Avillion is compensation and benefits system. It also shows that this factor has a significant relationship with the employee’s job turnover in Avillion Legacy Melaka hotel. Recommendations for future researcher are also been discussed.